A Pan-Cancer Analysis of the Oncogenic Role of Nuclear Transport Factor 2 in Human Cancers - Li, Yu; Huang, Yongsheng; Ren, Shuwei; Xiao, Xing; Cao, Haotian; He, Juan (Frontiers in Oncology, 2022)
Nuclear transport factor 2 (NUTF2) is a GDP binding protein which participates in the nucleocytoplasmic transport process. The role of NUTF2 in cancer development is largely unknown and lacks of systemic assessment across human cancers. In this study, we performed a pan-caner analysis of NUTF2 in human cancers. Out of 33 types of cancers, 19 types had significantly different expression of NUTF2 between tumor and normal tissues. Meanwhile, survival analysis showed that NUTF2 could be an independent prognostic factor in several tumor types. Further analysis suggested that the expression of NUTF2 expression was correlated with the infiltration of immune cells, such as CD8+ T cells, effector memory CD4+ T cells and cancer-associated fibroblasts in kidney renal clear cell carcinoma. Moreover, co-expression analysis showed the positive association between NUTF2 and cell proliferation biomarkers (MKI67and PCNA) and epithelial-mesenchymal transition markers (VIM, TWIST1, SNAI1, SNAI2, FN1 and CDH2), suggesting that NUTF2 plays important roles in regulating cancer proliferation and metastasis. This pan-caner analysis of NUTF2 provides a systemic understanding of its oncogenic role across different types of cancers.